AB0570 MIXED CONNECTIVE TISSUE DISEASE: NOT THAT UNCOMMON, A SINGLE-CENTER EXPERIENCE FROM INDIA. (2nd June 2020) - Dhir, V.; Jha, S.; Sharma, A.; Jain, S.; Sharma, S. K.; Naidu, G.
Abstract : Background: Mixed connective tissue disease (MCTD) is considered to be uncommon; specifically there is sparse data on MCTD from developing countries like India. Objectives: This study examines the clinical and serological features of these patients in a single center in North-India. Methods: This was a retrospective single-center study of patients diagnosed as MCTD in last 20 years. The patients included fulfilled at least one of the diagnostic criteria namely Alarcón-Segovia, Kasukawa, and Kahns. Demographic details, clinical signs and symptoms, laboratory parameters, treatment and outcome were extracted from medical records and clinic files in a pre-designed proforma. Results: This study included 41 MCTD patients. There was a marked female preponderance (F: M=40:1), and mean age of disease onset and diagnosis was 33.8 ± 10.7 and 39.3 ± 10.2 years. 39 (92%) of the patients fulfilled both Kahn and Kasukawa criteria, while 31 (76%) fulfilled Alarcon-Segovia criteria. Initially patients had been (mis)diagnosed as rheumatoid arthritis, systemic lupus erythematosus (or UCTD) (in five patients each), overlap syndromes or myositis (in 4 patients). ANA was commonly high-titer and specked, U1RNP was positive in all. (Table 1 ) Other autoantibodies on immunoblot included SSA and Ro52 in half the patients. Raynaud's was seen in three-fourth at presentation and all the patients over time. Digital gangrene and puffy fingers were seen in 8 (20%) and 18 (46%) patients. Other clinical features included arthritis in 33 (81%), sclerodactyly in 23 (56%) and proximal weakness in 20 patients (49%). Interstitial lung disease and pulmonary arterial hypertension were seen in 20 (57%) and 15 (44%) patients. All patients (except one) received prednisolone, and it was currently used in almost 90%. Intravenous cyclophosphamide was used in one-third, commonly for ILD. Conclusion: MCTD was not uncommon in the single-center in North India. Kahn and Kasukawa criteria were found to be the most sensitive for its diagnosis. Digital gangrene was relatively common and sometimes the presenting feature; whereas puffy fingers was present in only half the patients. Disclosure of Interests: None declared